A "groovy" diagnosis: Eosinophilic fasciitis. Issue 12 (15th July 2020) - Korsten, Peter
Abstract: Clinical examination can be the key to pursuing a diagnosis, even in rare diseases. The "groove sign" is a typical finding in eosinophilic fasciitis and can be elicited by elevation of the arm to allow for venous return with visible "grooving" of the veins due to skin thickening. Abstract : Clinical examination can be the key to pursuing a diagnosis, even in rare diseases. The "groove sign" is a typical finding in eosinophilic fasciitis and can be elicited by elevation of the arm to allow for venous return with visible "grooving" of the veins due to skin thickening.